2015
DOI: 10.18203/2320-1770.ijrcog20150737
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of serum uric acid, serum creatinine and serum cystatin C with maternal and fetal outcomes in rural Indian pregnant women

Abstract: BackgroundHypertensive disorders are the most common in pregnancy. Several studies showed a positive correlation between elevated maternal serum uric acid (UA), serum creatinine and adverse maternal and fetal outcomes, but only a few studies are available on serum cystatin C and maternal and fetal outcomes. The present study was undertaken to study the association of serum UA, creatinine and cystatin C with maternal and fetal outcomes.MethodsOut of 116 pregnant women 69 women had no hypertension and 47 had hyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 24 publications
(26 reference statements)
2
14
0
Order By: Relevance
“…Krishna S et al, Thanna et al, Yalamati P et al, concluded that high serum uric acid level could be a useful indicator of the maternal and fetal complication which is comparable to our study. [20][21][22] Hawkins TL et al, studied of hypertensive pregnant women (those with pre-eclampsia or gestational hypertension) the risk of adverse maternal outcome and adverse fetal outcome increased with increasing concentration of uric acid which is compared to our study. 23 …”
Section: Discussionsupporting
confidence: 48%
“…Krishna S et al, Thanna et al, Yalamati P et al, concluded that high serum uric acid level could be a useful indicator of the maternal and fetal complication which is comparable to our study. [20][21][22] Hawkins TL et al, studied of hypertensive pregnant women (those with pre-eclampsia or gestational hypertension) the risk of adverse maternal outcome and adverse fetal outcome increased with increasing concentration of uric acid which is compared to our study. 23 …”
Section: Discussionsupporting
confidence: 48%
“…In contrast, in a study from India including 116 pregnant women, high SUA were associated with low birthweight < 2.5 kg in crude analyses, but no longer after multivariable adjustment. Both markers analyzed in their study (SUA and creatinine), however, were associated with maternal hypertensive disorders in pregnancy [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Renal function, as assessed by cystatin C levels, a reliable marker for renal function, in pregnancy may also be indicators of maternal cardiometabolic disease [ 7 ] affecting fetal health. Several studies described the relationship between maternal SUA, renal function and fetal outcomes [ 8 12 ] and results are controversial.…”
Section: Introductionmentioning
confidence: 99%
“…Increased serum UA levels have been reported to be associated with hypertension, diabetes mellitus and metabolic syndrome (14-16). On the other hand, elevated serum UA concentrations have been observed in patients with pregnancy-related diseases, such as gestational hypertension, eclampsia and gestational diabetes mellitus (8,9,17). In our study, we found that serum UA was correlated with HRP score in advanced pregnant women.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, serum UA has been reported to be associated with various diseases such as cardiovascular disease, hypertension and metabolic syndrome (6). Previous study attested that serum UA was related with adverse pregnancy outcomes in pregnant woman with chronic glomerulonephritis (7), and serum UA concentrations have been found to be increased in patients with gestational hypertension and preeclampsia (8,9). Obviously, serum UA maintains a close association with pregnancy-related diseases.…”
Section: Introductionmentioning
confidence: 99%